Analisis Kinerja Keuangan Perusahaan Dengan Metode Du Pont System Pada PT. Kapuas Prima Coal - Nasahta, Anisha; Awotkay, Apolinaris S. (Jurnal Administrasi Karya Dharma, 2025)
This study aims to determine the company's financial performance using the Du Pont System, measured by NPM, TATO, ROI, and ROE at PT. Kapuas Prima Coal for the 2020-2023 period. This research is descriptive with a quantitative approach. The sampling technique used in this study was saturated sampling. The data source used in this study was secondary data in the form of PT. Kapuas Prima Coal's annual financial reports. The analysis results obtained by Net Profit Margin indicate that the company has not been able to optimize its performance in generating net profit. Total Asset Turnover is considered unhealthy because the company has not been able to generate revenue from its total assets. The Return on Investment is below industry standards, indicating the company is inefficient in utilizing all its assets to generate profits. Return on Equity indicates the company's inability to provide consistent returns to shareholders, with a positive value at the beginning of the period but then falling to a negative figure, affecting the financial performance of PT. Kapuas Prima Coal Tbk. The 2020-2023 period shows that the company is still in poor condition.